Effects of propolis supplementation on prooxidant-antioxidant balance, oxidative stress biomarkers, and body composition in obese patients with NAFLD: A double-blind randomized controlled clinical trial - Hamideh Nazari-Bonab; Mahlagha Nikbaf-Shandiz; Helda Tutunchi; Mehrangiz Ebrahimi-Mameghani (Health Promotion Perspectives)
Background: Oxidative stress is one of the main hits in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Propolis (PRP), a natural substance made by bees from plant extracts, has been reported to have antioxidant properties. The present clinical trial investigated the effect of Iranian PRP on prooxidant-antioxidant balance (PAB), oxidative stress biomarkers, and body composition in obese patients with NAFLD. Methods: In the present double-blind, randomized controlled clinical trial, 44 obese patients with NAFLD were randomly allocated to either Iranian PRP (1500 mg/d) or placebo (1500 mg/d) accompanied by a calorie-restricted diet (CRD) for eight weeks. PAB, oxidative stress biomarkers, and body composition were assessed at baseline and the end of the study. Results: There was a significant reduction in PAB levels over the trial in both groups. However, the between-group difference was not significant at the endpoint. At the end of the study, the inter-group comparison showed a significant decrease in serum glutathione peroxidase level in the placebo group compared to the PRP group after adjusting for confounding variables based on models 1 (P=0.027) and 2 (P=0.028). No significant within- or between-group differences in other studied oxidative stress biomarkers were found. Moreover, no between-group differences were observed for body composition and dietary intakes of energy and antioxidant micronutrients. Conclusion: Iranian PRP supplementation (1500 mg/d) for eight weeks could prevent the reduction of glutathione peroxidase levels compared to the control group. However, it could not affect other oxidative stress biomarkers, body composition, or dietary intakes of energy and antioxidant micronutrients.